Technology Innovation of Ginger Spring Machine as a Traditional Jamu for Coronavirus Prevention - Nely Ana Mufarida; ASROFUL ABIDIN (Universitas Muhammadiyah Sidoarjo, 2021)
The COVID-19 disease, including its prevention and treatment, is becoming a lively conversation in the community. There are many ways to protect yourself from the coronavirus. Apart from doing social distancing, consuming traditional drinks can also be a great way to increase endurance. Jamu has been a part of traditional Indonesian medicine for a long time. Herbal medicine is believed to provide a number of health benefits as well as to treat various diseases. Traditional spices are quite effective in maintaining endurance and are one of the solutions against the increasingly aggressive coronavirus (Covid-19) outbreak. Ginger drink is one of the traditional drinks that is easy to make and has the power to increase endurance to avoid the coronavirus (Covid-19). Ginger contains the bioactive compound gingerol which can fight the respiratory syncytial virus that causes respiratory infections. To make the ginger drink, it is necessary to squeeze ginger from the dregs. So far, the processing is done manually by using a grate and squeezing it by hand. People who grate get tired, especially if they have to grate large amounts of ginger. Based on this, appropriate technological innovations need to be applied to increase production yield and quality of squeezed ginger, namely by making the design of